Proactive Involvement of Local Population in Oil Spill Incidents: Gauging The Potential Of Informal Information Networks - Ventikos, Nikolaos; Thanopoulou, Helen; Georgoulis, George; Moulatzikos, Lambros (SPOUDAI Journal of Economics and Business, 2014)
The analysis of tanker accidents shows varied degrees and forms of involvement of local inhabitants at the different stages of specific events. The aim of the paper is to gauge, through a pilot survey, the potential of marine incident information networks among coastal or island populations within an accident setting. The authors review how reactions to tanker accidents of potentially affected populations may have an impact on the selection, design and implementation of the handling by the authorities of an evolving incident The paper argues that networks such as the Shore Awareness of Vessel Emergencies (S.A.V.E) proposed can eventually create a proactive mechanism to prevent chaotic reactions or disruption/distortion of the optimal response. A pilot survey was conducted to estimate population reactions to shipping accidents with a pollution risk and the willingness to participate in S.A.V.E type networks. The authors process data collected through questionnaires distributed to residents of a major maritime Greek island with a large number of active or retired seafarers. Questionnaire data are analyzed with an emphasis on gauging the degree of confidence in an unofficial but well-organized, network as S.A.V.E which would be based mainly on ad-hoc trained members from targeted parts of the local communities. JEL Classification: R41; Q28; Q58.